Article 15 of Regulation 2201/2003 and the transfer to a court better placed to hear the case. Comment to the ECJ Judgment 4 October 2018, IQ v JO, C-478/17 - Campuzano Díaz, Beatriz (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
This judgment refers to the interpretation of Article 15 of Council Regulation (EC) Nº 2201/2003 of 27 November 2003 concerning jurisdiction and the recognition and enforcement of judgments in matrimonial matters and the matters of parental responsibility, repealing Regulation (EC) No 1347/2000. The question was how to proceed in a situation characterised by the fact that the courts of both Member States concerned, had jurisdiction under this Regulation.